Current Status of Pediatric Ventricular Assist Device Support - Adachi, Iki; Burki, Sarah; Fraser, Charles D. (Seminars in thoracic and cardiovascular surgery. Pediatric cardiac surgery annual, 2017)
The last decade has witnessed significant advancement in the field of ventricular assist device (VAD) support. Although device options for pediatric patients were previously severely limited because of body size constraints, this frustrating situation has gradually been changing, owing to ongoing device miniaturization. Recognition of the superiority of VAD support compared with conventional extracorporeal membrane oxygenation support has spurred enthusiasm for VAD support in children. In this article, we discuss the current status of pediatric VAD support; where do we stand now and where will we be heading? Because this field is rapidly changing, it is anticipated that this article will provide a general overview of what is currently occurring in the field of pediatric VAD support.